Media Management Digital in Efforts to Improve the Quality of Biology Learning Education at Purnayudha High School, Labuhanbatu Regency - Risma Delima Harahap (Sinergi International Journal of Education, 2026)
This study aims to examine how digital media management is implemented to improve the quality of biology learning at Purnayudha Senior High School, Labuhanbatu Regency. Specifically, the research explores the strategies used by the school in managing digital media, the supporting and inhibiting factors influencing its implementation, and its contribution to improving the quality of biology learning. A qualitative descriptive approach was employed, with data collected through classroom observations, semi-structured interviews, and document analysis. The participants consisted of the school principal, biology teachers, and students involved in digital-based learning activities. Data were analyzed using thematic analysis through coding, categorization, and interpretation of recurring patterns. The findings show that digital media management has been systematically integrated into curriculum planning and classroom instructional practices. The improvement in the quality of biology learning is reflected in several aspects, including increased student engagement in learning activities, more interactive classroom communication, improved access to learning resources, and better support for visualizing biological concepts through digital media. The effectiveness of this implementation is supported by internal factors such as collaboration among school leaders, teachers, and students, alignment between the school’s vision and the integration of information technology, and the availability of technological facilities and infrastructure. External support is also provided by parents and partner institutions. However, challenges remain, particularly unstable internet connectivity and varying levels of digital competence among educators. To address these issues, the school continues to improve technological infrastructure and provide professional development programs to strengthen teachers’ capacity in integrating digital media into biology learning.